Genesia vaginal e dilatação vaginal: uma abordagem individualizada utilizando moldes de impressora 3D - Fernandes, Marina Silva [UNIFESP] (2021)
Objective: evaluate the use of vaginal molds, made with 3D printing, for conservative treatment through vaginal dilation in patients with Vaginal Agenesis. Material and methods: Eighteen patients with a diagnosis of vaginal agenesis (MRKHS, Total Androgen Insensitivity Syndrome and cervicovaginal agenesis), from the Female Genital Malformation Sector of the Gynecology Department of the Paulista School of Medicine of the Federal University of São Paulo, were selected. The production of the devices was carried out in a 3D printer and, as raw material, the polymeric filament of the lactic polyacid (PLA) was used. Results: Fifteen patients were treated with progressive vaginal dilation, with daily exercises of 20 minutes. The average initial vaginal length was 1.8 cm. Two cases of incidental urethral dilation were identified, and the technique was reoriented. Thirteen patients reached a final vaginal length of 6 cm or more. After 6 cm of vaginal length, they were released for sexual intercourse. The time required to reach the final vaginal length (minimum 6 cm) varied from 1 month to 12 months, with an average of 5.6 months. A personalized treatment was proposed and developed for each patient. The first choice of treatment for vaginal agenesis is vaginal dilation. The choice of molds for 3D printers was based on the possibility of offering individualized treatment, with low cost and low rate of complications. Conclusion: The present study has shown the good applicability of the devices, bringing an economical and easily reproducible option for the treatment of vaginal agenesis, making it a promising and accessible tool.